Resettlement and adjustment of Bhutanese refugees in the Kansas City metropolitan area - Anderson, Christina L. (Kansas State University, 2019)
Since 1980, the United States has resettled over 3 million refugees in large metropolitan areas from coast to coast. They arrive in the United States after being compelled to flee their homes and the United Nations High Commissioner on Refugees determines that third country resettlement is the only remaining option. This dissertation uses interviews with resettlement coordinators and Bhutanese refugees to probe some of the finer details behind refugee resettlement. The first question my dissertation answers is how Bhutanese refugees made critical migration decisions. My analysis concludes that decisions are often made at the household level, but social capital plays a significant role. Next, this dissertation explores the role of social capital in the Bhutanese resettlement experience. In particular, I focus on how Bhutanese refugees are integrating and interacting within their new host communities. My research found that the greatest barriers for Bhutanese refugees are experiencing underemployment and religious tensions. I also spent many hours with two sewing groups that provide a critical social outlet for isolated Bhutanese women. These groups are helping a small segment of the population adjust to their new life in the United States. Another key mechanism behind refugee resettlement are institutions, both governmental and non-governmental. Institutions determine which refugees are selected for resettlement and where they are resettled. Institutional involvement continues as they work beside refugees to ensure they become self-sufficient. My research also revealed that place is an essential component of successful refugee resettlement. Refugees that are resettled to cities with low rents and an abundance of low-skill jobs offer the greatest opportunities for self-sufficiency. Lastly, this dissertation explores how different generations of Bhutanese refugees experience the resettlement process. Refugees are often resettled as a large multi-generational family unit. This phenomenon provides a unique opportunity to explore assimilation from a different vantage point. At the conclusion of my dissertation, I hope my readers will have a deeper understanding and appreciation of refugees that are living in our surrounding neighborhoods.
Keywords: Bhutan; Refugee; Kansas City; Place; Migration theory; Assimilation